Nutrient loads exported from managed catchments reveal emergent biogeochemical stationarity - Basu, Nandita B.; Destouni, Georgia; Jawitz, James W.; Thompson, Sally E.; Loukinova, Natalia V.; Darracq, Amélie; Zanardo, Stefano; Yaeger, Mary; Sivapalan, Murugesu; Rinaldo, Andrea; Rao, P. Suresh C. (Geophysical research letters, 2010)
Complexity of heterogeneous catchments poses challenges in predicting biogeochemical responses to human alterations and stochastic hydro‐climatic drivers. Human interferences and climate change may have contributed to the demise of hydrologic stationarity, but our synthesis of a large body of observational data suggests that anthropogenic impacts have also resulted in the emergence of effective biogeochemical stationarity in managed catchments. Long‐term monitoring data from the Mississippi‐Atchafalaya River Basin (MARB) and the Baltic Sea Drainage Basin (BSDB) reveal that inter‐annual variations in loads (LT) for total‐N (TN) and total‐P (TP), exported from a catchment are dominantly controlled by discharge (QT) leading inevitably to temporal invariance of the annual, flow‐weighted concentration, = (LT/QT). Emergence of this consistent pattern across diverse managed catchments is attributed to the anthropogenic legacy of accumulated nutrient sources generating memory, similar to ubiquitously present sources for geogenic constituents that also exhibit a linear LT‐QT relationship. These responses are characteristic of transport‐limited systems. In contrast, in the absence of legacy sources in less‐managed catchments, values were highly variable and supply limited. We offer a theoretical explanation for the observed patterns at the event scale, and extend it to consider the stochastic nature of rainfall/flow patterns at annual scales. Our analysis suggests that: (1) expected inter‐annual variations in LT can be robustly predicted given discharge variations arising from hydro‐climatic or anthropogenic forcing, and (2) water‐quality problems in receiving inland and coastal waters would persist until the accumulated storages of nutrients have been substantially depleted. The finding has notable implications on catchment management to mitigate adverse water‐quality impacts, and on acceleration of global biogeochemical cycles.